If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1 = 2x + -37 Reorder the terms: -1 + 8x = 2x + -37 Reorder the terms: -1 + 8x = -37 + 2x Solving -1 + 8x = -37 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -1 + 8x + -2x = -37 + 2x + -2x Combine like terms: 8x + -2x = 6x -1 + 6x = -37 + 2x + -2x Combine like terms: 2x + -2x = 0 -1 + 6x = -37 + 0 -1 + 6x = -37 Add '1' to each side of the equation. -1 + 1 + 6x = -37 + 1 Combine like terms: -1 + 1 = 0 0 + 6x = -37 + 1 6x = -37 + 1 Combine like terms: -37 + 1 = -36 6x = -36 Divide each side by '6'. x = -6 Simplifying x = -6
| 4=2(y-5)-2 | | .4x-9=-7 | | (2x-7)(4x+12)=0 | | 5T=2T-12 | | 22+4x-14=0 | | -5.5=t+2 | | f(10)=100.3 | | 8x-3=4x+21 | | 3(2x-3)+3(3)=-7x | | 10x-.375-4x=6x | | 3a+1=-3(a-1) | | 6y+8y=10y | | 5x=a+b | | 7m+(m+2)=-24 | | 8y+4y=12y | | 1.4(5-.05)=2.8 | | c-2=6 | | 3x+5+2x=90 | | 0.5x-0.2=0.15 | | 3y+2y=5y | | -32=-5x+13x | | -c+9=-13 | | 3(2x-5)=15 | | 17-x=10+2(x+8) | | 2n=-15 | | -1=-3x+4 | | 8-8x=28-15x | | -11x-9x=100 | | 3x-8+2x+13=95 | | b=3x+3b | | 7c+3-5c=12 | | 2r+20= |